Metabolites Alterations in the Medial Prefrontal Cortex of Methamphetamine Users in Abstinence: A 1H MRS Study - Wu, Qiuxia; Qi, Chang; Long, Jiang; Liao, Yanhui; Wang, Xuyi; Xie, An; Liu, Jianbin; Hao, Wei; Tang, Yiyuan; Yang, Baozhu; Liu, Tieqiao; Tang, Jinsong (Frontiers in Psychiatry, 2018)
Abstract Background：The medial prefrontal cortex (mPFC) contains various neurotransmitter systems and plays an important role in drug use. Broad body of literature on how methamphetamine (MA) affects the structure and metabolism in the animal’s mPFC is emerging, while the effects on metabolites of mPFC among human is still unclear. In this study, proton magnetic resonance spectroscopy (¹H MRS) was used to measure metabolites of mPFC in methamphetamine dependent subjects. Methods：Sixty-one subjects with a history of MA dependence (fulfiled the Diagnostic and Statistical Manual of Mental Disorders, fourth edition criteria) and 65 drug-naïve control subjects (age19-45) completed ¹H MRS scans using 3.0T Siemens MRI scanner. Single voxel spectra were acquired from the mPFC bilaterally using a point resolved spectroscopy sequence (PRESS). The ¹H MRS data were automatically fit with linear combination model for quantification of metabolite levels of n-acetyl-aspartate (NAA), myo-inositol (mI), glycerophosphocholine plus phosphocholine(GPC+PC) , phosphocreatine plus creatine (PCr+Cr), and glutamate (Glu). Metabolite levels were reported as ratios to PCr+Cr. Results: The MA group showed a significant reduction in NAA/PCr+Cr ratio and elevation in Glu/PCr+Cr ratio and mI/PCr+Cr ratio, compared with healthy control. No significant correlation was found between metabolite ratios and MA use variables. Conclusions: MA use is associated with a significant increased Glu/PCr+Cr ratio, mI/PCr+Cr ratio and reduced NAA/PCr+Cr ratio in the mPFC of MA dependence subjects. These findings suggest that Glu may play a key role in MA induced neurotoxicity. Key words: methamphetamine, mPFC, NAA, Glu, mI, ¹H MRS